The Impact of Adolescent Resilience on Mobile Phone Addiction During COVID-19 Normalization and Flooding in China: A Chain Mediating - Ma, Anna; Yang, Yan; Guo, Shuangxi; Li, Xue; Zhang, Shenhua; Chang, Hongjuan (Frontiers in Psychology, 2022)
Natural disasters are known to cause long-term psychological problems and increase substance use in some adults; however, it is unclear whether disasters lead to these problems also in adolescents. We hypothesized that experiencing both a major flood and the COVID-19 pandemic would influence adolescent resilience related to mobile phone addiction. We tested the mediating role of coping style and depression, anxiety, and stress (DASS) on phone addiction among 1751 adolescents in the Henan Province. The adolescents were surveyed via an online questionnaire, and we used structural equation modeling to examine the correlations and moderation effects. The results show that both coping style and DASS could mediate the relationship between adolescent resilience and mobile phone addiction among Chinese adolescents. The relationship between adolescent resilience and mobile phone addiction in Chinese adolescents was mediated by the chain of coping styles and DASS.